Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1016/j.clpt.2005.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Acid-suppressive effects of rabeprazole, omeprazole, and lansoprazole at reduced and standard doses: A crossover comparative study in homozygous extensive metabolizers of cytochrome P450 2C19

Abstract: Rabeprazole, omeprazole, and lansoprazole, given once daily at standard doses, cannot be expected to achieve ideal acid suppression for the initial therapy for gastroesophageal reflux disease in Helicobacter-negative CYP2C19 homozygous extensive metabolizers. Rabeprazole 10 mg may be appropriate for step-down therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 61 publications
1
35
3
Order By: Relevance
“…However, a single dose of not 10 mg but 20 mg rabeprazole was compared among CYP2C19 genotypes. These results slightly differ from those of previous reports [16,[18][19][20]36] in which rabeprazole induced an earlier rise in the intragastric pH than other PPIs. However, most previous studies examined the effects after the administration of 20 mg rabeprazole or other PPIs on days 3 -7 [16,[18][19][20]36], not the early postadministration phase (1 -12 h) of a single dose.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, a single dose of not 10 mg but 20 mg rabeprazole was compared among CYP2C19 genotypes. These results slightly differ from those of previous reports [16,[18][19][20]36] in which rabeprazole induced an earlier rise in the intragastric pH than other PPIs. However, most previous studies examined the effects after the administration of 20 mg rabeprazole or other PPIs on days 3 -7 [16,[18][19][20]36], not the early postadministration phase (1 -12 h) of a single dose.…”
Section: Discussioncontrasting
confidence: 57%
“…The acid-inhibitory effects of PPIs are significantly dependent on the genotype status, as well as on their intrinsic pharmacokinetic and pharmacodynamic charac-teristics and dosing schemes [10,[17][18][19][20]. The effect of omeprazole on the suppression of gastric acid secretion was related to the area under the time-plasma concentration curve (AUC) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Achieving sufficient gastric acid secretion-inhibiting effects is important, and a correlation is thought to exist between gastric pH and the success of H. pylori eradication therapy (14). RPZ is known to increase gastric pH to between 6 and 8 more rapidly and reliably than other PPIs and to effectively inhibit nocturnal secretion of gastric acid (15)(16)(17)(18)(19). The CYP2C19 genotype is also known to be a factor that affects the eradication rate (20).…”
Section: Discussionmentioning
confidence: 99%
“…31 The median values of the 24-hour percent time for pH>4 of HomEM were 59% in 20 mg rabeprazole and 56% in 30 mg lansoprazole. 32 There were 3 clinical studies 25,26,28 that directly compared H. pylori eradication rates of lansoprazole and rabeprazole according to CYP2C19 polymorphism. Although these studies had relatively small sample size and insufficient randomization, they all reported no significant differences of eradication rate between lansoprazole and rabeprazole group according to each CYP2C19 polymorphism.…”
Section: Discussionmentioning
confidence: 99%